Enumerator Characteristics and Reporting Bias - Measures for Advancing Gender Equality (MAGNET) Initiative (International Food Policy Research Institute, 2024)
The Measures for Advancing Gender Equality (MAGNET) initiative aims to broaden and deepen the measurement of women’s agency, based on the development of new tools and rigorous testing and comparison of both new and existing methods for measuring agency, and promoting the adoption of these measures at scale. By increasing the availability of innovative meaningful measures of agency for a broad range of contexts, we hope our work will lead to an improved understanding of what women’s agency is, how it manifests and how it can best be measured across contexts given the research question at hand. Evidence suggests that men’s and women’s responses may be affected by the interview context. This tool allows identifying which enumerators’ characteristics (e.g., gender, age, beliefs on women’s rights) affect respondents’ reporting and whether there are heterogeneities across genders and contexts. This tool, Enumerator Characteristics and Reporting Bias, should be administered to the enumerators before enumerators’ training takes place and can be used to assess the need to randomize enumerators, design interventions at the enumerator-level, or control for enumerator characteristics while analyzing the survey data.